A feasibility study in establishing Marjoram's Place at San Sebastian College-Recoletos in Cavite City - Dy, Marie Rose R., author; Figueroa, Angeline C., author; Goingo, Diana Monica J., author; Ventura, Elizabeth A., adviser (Rosario, Cavite : Cavite State University-CCAT Campus, 2004)
Thesis Abstract
A Feasibility Study (BSHRM)--Cavite State University-CCAT Campus, 2004.
Includes bibliographical references and appendices.
In English text.
Keywords: Food service concessionaire; Specialty BBQ; Self-service.; Quality service; Nutritious foods; Variety of foods; Affordable prices; Feasibility study; Healthy options